Galloway–Mowat Syndrome Type 3 Caused by OSGEP Gene Variants: A Case Report and Literature Review - Xu, Suhua; Hu, Lan; Yang, Lin; Wu, Bingbing; Cao, Yun; Zhang, Rong; Xu, Xin; Ma, Haiyan; Zhou, Wenhao; Cheng, Guoqiang; Zhang, Peng; Hu, Liyuan (Frontiers in Pediatrics, 2022)
Background Galloway–Mowat syndrome type 3 (GAMOS3) is an extremely rare and severe autosomal-recessive disease characterized by early-onset nephrotic syndrome (NS), microcephaly and neurological impairment. Reported GAMOS cases have gradually increased since pathogenic OSGEP variants were identified as the aetiology in 2017. Methods Using whole-exome sequencing and a data analysis process established by Children's Hospital of Fudan University, the clinical and molecular features of 3 infants with OSGEP mutations were summarized. Literature regarding the clinical features of GAMOS3 caused by OSGEP variants was reviewed. Results Thirty-seven individuals (3 from this study) from 34 families were included. Twenty-two different OSGEP variants were identified. The c.740G>A (p.Arg247Gln) variant in OSGEP was detected in 15 families (44%), all from Asia. Most affected individuals (including patients I and II in this study) showed a typical phenotype, including microcephaly (92%) with brain anomalies (97%), developmental delay (81%), congenital NS (54%), and craniofacial (94%) and skeletal dysmorphism (84%). Renal manifestations varied from proteinuria (94%, median onset = 1.5 months) to NS (83%) and end-stage renal disease (48%, 11 months) during follow-up. Patients with congenital NS had a lower survival probability (median survival time = 3 months) than those without congenital NS (78 months) (P < 0.01, log-rank test). Conclusion GAMOS3 is a progressive renal-neurological syndrome with a poor prognosis, especially with congenital NS. Microcephaly with dysmorphic features are vital clues to further evaluate renal impairment and brain anomalies. Timely molecular diagnosis is crucial for clinical decision-making, appropriate treatment and genetic counselling.